Análise da função cardíaca de girinos de rã-touro, Lithobathes catesbeianus, expostos a piretrina, associada ou não a nanopartículas - Deluno Garcia, Thais (2018)
The increasing use of agrochemicals has been causing several environmental disturbances. As a result, botanical insecticides, such as pyrethrum (PYR), have been created because they are considered biodegradable and less toxic to non-target organisms. Indeed, the modified release of these biocides through systems carriers, for example nanoparticles, is another theoretically less harmful. To test the hypothesis that PIR, when associated to solid lipid nanoparticles (SLN) becomes less toxic to bullfrog tadpoles (Lithobates catesbeianus), the in situ heart rate (ƒH - bpm), activity level (AL -% of total animals), relative ventricular mass (RMV -% body mass), diameter of cardiac myofibrils, in addition to the genotoxicity analysis by means of the micronucleus test and other cellular abnormalities and the evaluation of possible alterations of the cutaneous and internal pigmentation of the heart were analyzed in response to PIR and SLN isolated or in association. The determination of the LC50 48h for the pyrethrum was previously performed and, thereafter, a sublethal concentration corresponding to 1/5 of the LC50 of 400 μg.L-1 (80 μg.L-1) was used. The SLN used in the present study had an average size of 324 nm when isolated and 258 nm when associated (NLS + PIR), with a polydispersity index of 0.19 for NLS and 0.11 for SLN + PIR and potential zeta of -11 mV for SLN and -10 mV for SLN + PIR. No changes in ƒH and RVM (P> 0.05), indicating that these biomarkers are not sensitive enough to respond to the sublethal concentration used, in addition to the short exposure period (48h). However, the diameter of the myofibrils of the group SLN alone was lower (P = 0.0104) than that of the control (CT), there was also a difference between PIR and NLS (P = 0.0146). Thus, despite the subcellular changes in cardiomyocytes (decrease in myofibrils’ diameter), they did not result in cardiac atrophy (MVR). The AL of PIR group (12.5 ± 4.1%) was lower (P = 0.0350) than that observed for CT (38.5 ± 8.8%). This lethargy corroborates the neurotoxicity of PIR already reported for other species and its reversal when the PIR was associated with the SLN indicates a protective effect of the SLN for this biomarker. An increase in the number of micronucleated erythrocytes for the SLN (P = 0.0001) and SLN + PIR (P = 0.001) compared to CT was observed, and there was also a difference between PIR and SLN (P = 0.0332). It was also observed an increase in the occurrence of binucleated erythrocytes (P = 0.0452) for SLN in relation to CT. Therefore, SLN when isolated showed genotoxic effects, but when associated to PIR (SLN + PIR) its toxic effects were less drastic. Exposure to all groups increased tadpoles’ skin pigmentation, pointing this biomarker as the one of greater ecological relevance, since it is not necessary to euthanize organisms. This response seems to exert a protective effect on the internal organs, since the pigmentation of the heart did not increase in the SLN or in SLN + PIR in relation to CT. These results indicate that while some biomarkers are irresponsive to PIR or SLN, others are particularly negatively impacted by PIR isolated that, when associated with SLNs has its deleterious effects diminished or reversed, the inverse also being true. These results highlight the need to use a wide range of biomarkers at different levels of organization (from the subcellular to the individual) to have a more accurate view of the effect of xenobiotics on non-target organisms and the possible role played by nanoparticles.